Russel Taylors / Nur Iman Kamarudin Azhar - Kamarudin Azhar, Nur Iman (2022)
Russell Taylors is a local company which focusing on the diversified, market-driven consumers’ products brand. This company provides a masterful design, to precise engineering, robust testing and global certification of kitchen gadgets and equipment that make cooking even easier and safer. In this company analysis, it is focusing on the Air fryer that is produced by the Russell Taylors manufacturing to be investigate, identified, and analyzed along with their current problems and come out with solutions. The first problem regarding their product is the bad odor that caused by the cooking protein when using the Air Fryer. Though it may sound like a harmless issue, however certain consumers are very sensitive towards strong odor that may bring distress and discomforts towards them. For example, people with chronic migraine and pregnant women. These group of people who are experiencing various of changes in their body due hormones, genetic, hypersomnia, environmental or the result of benzodiazepine withdrawal syndrome that cause them to be extremely sensitive to smell which may result in feeling nauseous and vomiting. Other than that, the cooking method may ruin the food texture as the technology of the Air Fryer is to be oil-less. Though the apparatus of the appliance also includes non-sticky tray, however some proteins do not suit with the tray which cause the texture of it to be damaged and breakable. This issue may vandalize the presentation of the food. Aside from that, there are few solutions to these problems, which primarily can be done with improvement, Research and Development, and convert their raw material (coating of Teflon to create non-sticky tray) with new alternative such as ceramic. These materials are heat resistant, last in the long run, and safer as it does not contain any coating of chemicals. Furthermore, to eliminate the bad odor from the Air Fryer is to improve the appliance by an engineered material consisting of micro sized particle that capture and physically bind odor-causing compounds or catalytically convert the odor molecules into non-odorous molecules from the Air Fryer.